Recent results on Heavy-Ion induced reactions of interest for 0νββ decay. (August 2019) - Agodi, C.; Cappuzzello, F.; Acosta, L.; Altana, C.; Amador-Valenzuela, P.; Auerbach, N.; Barea, J.; Bellone, J.I.; Bijker, R.; Bonanno, D.; BorelloLewin, T.; Boztosun, I.; et al.
Abstract: An updated overview of recent results on Heavy-Ion induced reactions of interest for neutrinoless double beta decay is reported in the framework of the NUMEN project. The NUMEN idea is to study heavy-ion induced Double Charge Exchange (DCE) reactions with the aim to get information on the nuclear matrix elements for neutrinoless double beta (0νββ) decay. Moreover, to infer the neutrino average masses from the possible measurement of the half- life of 0νββ decay, the knowledge of the nuclear matrix elements is a crucial aspect.